Close Encounters of the Third Domain: The Emerging Genomic View of Archaeal Diversity and Evolution - Spang, Anja (Hindawi Publishing Corporation, 2013)
The Archaea represent the so-called Third Domain of life, which has evolved in parallel with the Bacteria and which is implicated to have played a pivotal role in the emergence of the eukaryotic domain of life. Recent progress in genomic sequencing technologies and cultivation-independent methods has started to unearth a plethora of data of novel, uncultivated archaeal lineages. Here, we review how the availability of such genomic data has revealed several important insights into the diversity, ecological relevance, metabolic capacity, and the origin and evolution of the archaeal domain of life.